Urinary Dicarboxylic Acid Excretion in Formula-Fed Infants. (April 2015) - Taylor, Haley; Eliot, Kathrin; Shoemaker, James; Kelly, Patrick
Purpose . The common practice of medium-chain triglyceride (MCT) feeding has been associated with high urinary dicarboxylic acid excretion levels in infants. The purpose of this study was to investigate the effect of MCT supplementation on urine metabolite excretion by infants on different formulas. Methods . Urine sample data from a Metabolic Screening Laboratory were provided, medical records were accessed to record infant formula, and ingredient lists of formulas were reviewed. The urinary acid profiles were compared based on the percentage of fat content coming from MCT. Results . A MANOVA was conducted and there was a statistically significant effect of acid profiles. Pairwise comparisons indicate a significant difference between high and low %MCT ( P = .0002), low and medium %MCT ( P = .0156), and high and low/medium %MCT ( P = .0030) for adipic acid. For both suberic acid and sebacic acid, there was a significant difference between high and low %MCT ( P = .0001), high and medium %MCT ( P = .0001, P = .0015), and high and low/medium %MCT ( P = .0001). This study suggests that relative amounts of dicarboxylic acids cannot be used alone as a diagnostic criteria. The exact amount of MCT in each formula needs to be considered.